2018
DOI: 10.1111/mec.14901
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variations in microbial diversity across the three domains of life in a tropical thalassohaline lake (Dziani Dzaha, Mayotte Island)

Abstract: Thalassohaline ecosystems are hypersaline environments originating from seawater in which sodium chloride is the most abundant salt and the pH is alkaline. Studies focusing on microbial diversity in thalassohaline lakes are still scarce compared with those on athalassohaline lakes such as soda lakes that have no marine origin. In this work, we investigated multiple facets of bacterial, archaeal and eukaryotic diversity in the thalassohaline Lake Dziani Dzaha using a metabarcoding approach. We showed that bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 69 publications
3
51
0
Order By: Relevance
“…In previous studies, it has been reported that the season and/or the depth in the lake can influence its microbial diversity (Bernard et al, 2019;Hugoni et al, 2018). To see whether the two FLA isolates were influenced by these parameters, we performed a specific qPCR on DNA isolated from the water lake sampled in April (end of the rainy season) and November (dry season) 2015.…”
Section: Amoeba Isolates Distribution In the Lakementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it has been reported that the season and/or the depth in the lake can influence its microbial diversity (Bernard et al, 2019;Hugoni et al, 2018). To see whether the two FLA isolates were influenced by these parameters, we performed a specific qPCR on DNA isolated from the water lake sampled in April (end of the rainy season) and November (dry season) 2015.…”
Section: Amoeba Isolates Distribution In the Lakementioning
confidence: 99%
“…Lake water is warm (29-35°C) over the whole year and depth; pH is alkaline, classically between 9 and 9.5 depending on the season. The lake Dziani Dzaha microbial planktonic community has recently been described via a metabarcoding approach (Hugoni et al, 2018). Bacterial and archaeal diversity was influenced mainly by the sampling depth, whereas dry and rainy seasons alternations drove changes in vertical segregation of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Dziani Dzaha is a shallow tropical volcanic crater lake on the Petite Terre Island of Mayotte (Comoros Archipelago, Indian Ocean) 28 , which is located 50 km west of a huge submarine volcano triggered in 2018 29 . Several surveys have been conducted to determine the lake biological, physical and chemical characteristics [30][31][32][33][34] (see details in Supplementary Information and Supplementary Fig. S1).…”
mentioning
confidence: 99%
“…The water temperature is of ≈ 30 °C with little depth and seasonal variations. The ecosystem biomass is extremely high 30 and it is limited to microbial organisms 34 , with stromatolitic constructions thriving in the shallow parts of the lake (Supplementary Information).…”
mentioning
confidence: 99%
See 1 more Smart Citation